1998
DOI: 10.1016/s0741-5214(98)70129-6
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of heparin-induced antibodies in patients undergoing vascular surgery: A prospective study

Abstract: Heparin-induced antibodies occur infrequently after peripheral vascular surgery. The commonly observed, mild degree of postoperative thrombocytopenia does not appear to be caused by heparin-induced antibodies. These results indicate that a standard dose of heparin for intraoperative anticoagulation during vascular surgery is not associated with a significant risk of heparin-induced thrombocytopenia and thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…An even lower incidence of heparin-induced antibodies by heparin-PF4 was identified in a prospective study of 54 patients after peripheral vascular surgery. 9 In this study, only 1.9% of patients converted to a positive antibody status after surgery, most of whom underwent carotid endarterectomy. These patients had not been recently exposed to heparin since this surgery was performed without preoperative arteriography (during which flushing of sheaths and catheters with heparinized saline is routine).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…An even lower incidence of heparin-induced antibodies by heparin-PF4 was identified in a prospective study of 54 patients after peripheral vascular surgery. 9 In this study, only 1.9% of patients converted to a positive antibody status after surgery, most of whom underwent carotid endarterectomy. These patients had not been recently exposed to heparin since this surgery was performed without preoperative arteriography (during which flushing of sheaths and catheters with heparinized saline is routine).…”
Section: Discussionmentioning
confidence: 58%
“…5 In contrast, prospective studies of the formation of heparin-induced antibodies after heparin use for other conditions indicates a much lower incidence. [7][8][9] Using the 14 C-labelled serotonin release assay, Warkentin and colleagues 7 showed a 7.8% incidence of heparin-induced immunoglobulin G (IgG) antibodies in 333 patients receiving Jackson Delayed-Onset Heparin-Induced Thrombocytopenia unfractionated heparin for DVT prophylaxis after hip surgery. Kappers-Klunne and colleagues 8 demonstrated elevated heparin-PF4 ELISA for IgG in 2.5% and IgM in 2.0% of 358 patients treated with systemic heparin anticoagulation for coronary or neurologic ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, none of the patients developed thromboembolic complications. In 1998, Jackson et al 10 performed a prospective trial of 54 patients undergoing peripheral vascular surgery (66% carotid endarderectomy and 20% aortic reconstruction). All patients were tested before and after surgery for IgG antibodies to the complex of heparin‐platelet factor 4 using an ELISA method.…”
Section: Discussionmentioning
confidence: 99%
“…Jackson and colleagues evaluated the development of H-PF4 antibodies in 54 patients using ELISA. 15 The authors found that only one subject converted to positive after surgery; one thrombotic complication also occurred that was independent of the patient's ELISA status; however, no functional platelet tests were performed in these series. Lindhoff-Last and colleagues reported their experience with 50 patients undergoing vascular surgery.…”
Section: Hit In Vascular Surgerymentioning
confidence: 91%